Engaging STEM Education for High School Student in Japan: Exploration of Perception to Engineer Profession - Sulaeman, Nurul Fitriyah; Putra, Pramudya Dwi Aristya; Mineta, Ippei; Hakamada, Hiroki; Takahashi, Masahiro; Ide, Yuhsuke; Kumano, Yoshisuke (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2020)
While Science-Technology-Engineering-Mathematics (STEM) education is expanding worldwide, engineering reminds as both valuable and difficult element to integrate. Understanding students’ perceptions of the engineering profession might be key to enhancing their interest in engineering careers in the future and insight to science educators who demand to develop more STEM activities in their classroom. In our framework, a case study was used to explore the perceptions of 16 students (aged 14-15) as they participated in STEM activities at Japan Junior High School. After participating in the activities, students completed an open-ended questionnaire about the profession. Data analysis was guided by a focus on general perceptions of engineering, the clustering of those perceptions, and discussions of how the perceptions related to the literature. Text analysis was conducted, especially in terms of frequency network and hierarchical cluster analysis. Our findings indicate that students’ perceptions were related to making or creating, technology, and machines. Five clusters of responses were found. The “design, make, develop new technology” and “solve the problem faced by society” clusters were influential. There were disparities between the students’ perceptions and the definition of engineering, especially regarding constraints and the use of science and mathematics concepts.